Monitoring Tacrolimus Trough Concentrations During the First Year After Kidney Transplantation: A National Retrospective Cohort Study - Alghanem, Sarah S.; Soliman, Moetaza M.; Alibrahim, Ali A.; Gheith, Osama; Kenawy, Ahmed S.; Awad, Abdelmoneim (Frontiers in Pharmacology, 2020)
Background: There is lack of data in the literature on the evaluation of tacrolimus (TAC) dosage regimen and monitoring after kidney transplantation (KT) in Kuwait. The aim of the present study was to evaluate physicians’ adherence to the hospital protocol, achievement of target TAC trough concentration (C0), the prevalence of TAC side effects (SEs) namely post-transplant diabetes mellitus (PTDM), denovo hypertension (HTN) and dyslipidemia, and factors associated with the occurrence of these SEs among KT recipients in Kuwait. Methods: A retrospective study was conducted among 298 KT recipients receiving TAC during the first year post-transplantation (PT). Descriptive and multivariate logistic regression analyses were used. Results: The initial TAC dosing as per the local hospital protocol was prescribed for 28.2% of patients. The proportion of patients that had C0 levels within the target range increased from 31.5% to 60.3% during week 1 to 52. Among patients who did not have HTN, DM, or dyslipidemia before using TAC, 78.6%, 35.2%, and 51.9% of them were prescribed antihypertensive, antidiabetic, and antilipidemic medications during the follow-up period. Age ≥40 years was significantly associated with development of de novo HTN, dyslipidemia, and PTDM (p<0.05). High TAC trough concentration/daily dose (C0/D) ratio was significantly associated with development of PTDM (p<0.05). Conclusion: Physicians’ adherence to the local hospital protocol was low. Less than two-fifths of patients achieved target TAC C0 levels during the first month PT. SEs were more common in older patients. These findings warrant efforts to implement targeted multifaceted interventions to improve TAC prescribing and monitoring after KT.